Răspuns :
1 + √5 - √4 = 1 + √5 - 2 = √5 - 1
1 / ( √5 -1) = 1 ·(√5 + 1) / ( √5 - 1 ) ·(√5 + 1) =
= ( √5 + 1 ) / [ √5² - 1² ]
= ( √5 + 1 ) / [ 5 - 1 ]
= ( √5 + 1 ) / 4
1 / ( √5 -1) = 1 ·(√5 + 1) / ( √5 - 1 ) ·(√5 + 1) =
= ( √5 + 1 ) / [ √5² - 1² ]
= ( √5 + 1 ) / [ 5 - 1 ]
= ( √5 + 1 ) / 4
1 : (1 + √5 - √4) = 1 : (1 + √5 - 2) = 1 : (√5 - 1) (*)
√4 = 2.
Amplificam relatia (*) cu √5 + 1 si obtinem:
(√5 + 1) : [(√5 - 1) (√5 + 1)] = (√5 + 1) : (√5² - 1²) = (√5 + 1) : (5 - 1) =
= (√5 + 1) : 4.
Am utilizat formula (a - b) (a + b) = a² - b².
√4 = 2.
Amplificam relatia (*) cu √5 + 1 si obtinem:
(√5 + 1) : [(√5 - 1) (√5 + 1)] = (√5 + 1) : (√5² - 1²) = (√5 + 1) : (5 - 1) =
= (√5 + 1) : 4.
Am utilizat formula (a - b) (a + b) = a² - b².